MiR-585-5p impedes gastric cancer proliferation and metastasis by orchestrating the interactions among CREB1, MAPK1 and MITF - Wang, Yunwei; Li, Ming; Zeng, Jiaoxia; Yang, Yunshu; Li, Zengshan; Hu, Sijun; Yang, Fangfang; Wang, Na; Wang, Wenlan; Tie, Jun (Frontiers in Immunology, 2022)
MicroRNAs (miRNAs) were found to drive gastric cancer (GC) progression. However, the hidden pathogenesis that govern GC development remains uncertain. MiR-585-5p is highly downregulated within GC tissue, which was inversely linked to clinical prognosis. And we verified that miR-585-5p could effectively hinder proliferative / metastatic properties by synchronously targeting cyclic AMP-responsive element-binding protein 1 (CREB1), mitogen-activated protein kinase 1 (MAPK1) and microphthalmia-associated transcription factor (MITF). Furthermore, this investigation confirmed CREB1 activates MITF transcription and MAPK1 enhances MITF pro-cancerous activity via phosphorylation (Ser73), manifesting MITF acts as core target for miR-585-5p exerting effects. MiR-585-5p can not only inhibit MITF expression directly or indirectly, but also impede MITF activity in a MAPK1-dependent manner. In conclusion, this study unearthed miR-585-5p hampers GC proliferative / metastatic properties by orchestrating the interactions among CREB1, MAPK1 and MITF.